CURRICULUM AS CULTURAL ACCULTURATION - Aslan; Hifza; Abdul Wahab Syakhrani; Rif’an Syafruddin; Hadisa Putri (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2020)
Curriculum is change, which change is to answer the challenges of the times, according to the impact of cultural acculturation that is developing. The research in this study is a qualitative study with a document review. The results of this study, that each of the curriculum characteristics want to be changed, there are always weaknesses so that they want to be embroidered and want to be patched, so that the curriculum is more perfect, both from the teaching staff and the outputs produced by educational institutions. In fact, the nature of curriculum changes is in accordance with technological developments. When the curriculum changes, technology changes, but the teaching staff does not change, so the teacher experiences a dilemma. On one hand, teachers are required to teach according to curriculum changes, but on the other hand, students are more knowledgeable in technology than their teachers. The curriculum has changed, but the teaching style of the teacher has not changed, so what the teacher teaches does not match the characteristics of children in the current millineal generation. The curriculum is only capable of releasing a negative culture from the impact of technology, without as a whole.